STRATEGI PEMBELAJARAN TIK OLEH E-KOMUNITAS TERHADAPPELAKU INDUSTRI KREATIFDIYOGYAKARTA - Ardianto, Noor Indra (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
"As the rapid spread of Internet in Indonesia, proliferation of communities begin to show up in cyberspace. This is one form of actualization of the community as a form of internet use. The use of ICT inevitably also formed a distinct community among the creative industries, here we can see the e-communities comes into play. However, the development of ICT utilization has not been followed by a good learning about ICT itself, therefore instructional strategy for ICT education committed to the community is urgently needed, especially for the the creative industry players so that the education of ICT can be delivered more systematic, effective and efficient. Also the intended learning objectives can be achieved and new information provided from these e-communities can be absorbed well by the creative industries"